IS PEER-LED PALLIATIVE CARE TEACHING EFFECTIVE AND ACCEPTABLE?. Issue Volume 4: Issue (2014)Supplement 1 (1st March 2014) - Porteous, Anna; Paxton, Ann; MacCormick, Fiona
Abstract : Background: Peer-assisted learning is an established and validated approach to undergraduate education. The peer approach to educating qualified doctors, however, is in its infancy. As such, evidence of the efficacy and acceptability of this educational model is only just emerging. A peer-led Palliative Care study day has been developed by Specialty Trainees in Palliative Medicine in the North East of England and has provided education to five cohorts of junior doctors. Aims: To evaluate the efficacy of a peer-led Palliative Care teaching programme, in terms of knowledge and confidence gained. To evaluate the acceptability of a peer-led Palliative Care teaching programme, specifically in comparison with consultant-led teaching. Methods: Participants' knowledge and confidence was assessed before and after the study day, using a Multiple Choice Questionnaire (MCQ). Participants in the most recent cohort completed a questionnaire evaluating the acceptability of peer-led teaching. Results: Combining data from two consecutive study days, the MCQ knowledge scores of 48 participants rose from 50% to 87%. Participants' confidence in managing patients with palliative care needs rose by 38%. All participants reported the teaching to be comparable to, or more effective than consultant-led teaching. Twelve out of 13 participants found peer teachers to be more approachable than consultants. More than half found the relevance, content, preparation and organisation to be more effective than consultant-led teaching. Conclusions: We demonstrate that peer-led teaching is an effective and positively evaluated method of teaching junior doctors. Successful education relies upon the ability to create a non-threatening atmosphere conducive to learning and the grounding of content in relevant, contextual material. This may be better judged by peers than consultants. Research to assess sustained educational impact, benefits to peer teachers, and economic advantages of this approach would further enhance the application of this developing model in postgraduate clinical education.